Marketing in travel and tourism / Victor T.C. Middleton, Alan Fyall and Michael Morgan ; with contributions from Ashok Ranchhod - Middleton, Victor T. C.
"Marketing in Travel and Tourism aims to guide and support readers through the complexities of tourism marketing in the 21st C. It sets out clear explanations of marketing principles and concepts adapted from mainstream services marketing, and goes on to illustrate the range of applications currently practised in the modern visitor economy. Now in its fourth edition, and reprinted almost every year since 1988, each chapter of the book has been updated to include current evaluations of all the key developments in marketing, especially consumer centric marketing and the now focal role of the Internet in the marketing mix. The chapters on communicating with cutomers have been extensively rewritten to take account of e-marketing and related marketing developments in tourism that are pulled together in a forward looking Epilogue"